2017
DOI: 10.4103/neuroindia.ni_1136_15
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the recovery profiles of desflurane and isoflurane anesthesia in patients undergoing elective supratentorial craniotomy: A randomized controlled trial

Abstract: Desflurane significantly reduced emergence times, and was able to facilitate an early neurological examination for patients. Additional studies are required to establish the impact of inhalational agents on transient postoperative neurological deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 1 publication
1
21
0
Order By: Relevance
“…These were significantly shorter in the desflurane group in comparison to those in the isoflurane group. In agreement with these findings, Paul et al, 22 found that desflurane significantly reduced emergence times, thereby facilitating an early neurological examination for patient. Kaye et al, 7 reported that neurosurgical patients when anesthetized with desflurane opened their eyes and obeyed commands 50% faster than those receiving isoflurane.…”
Section: Discussionmentioning
confidence: 57%
“…These were significantly shorter in the desflurane group in comparison to those in the isoflurane group. In agreement with these findings, Paul et al, 22 found that desflurane significantly reduced emergence times, thereby facilitating an early neurological examination for patient. Kaye et al, 7 reported that neurosurgical patients when anesthetized with desflurane opened their eyes and obeyed commands 50% faster than those receiving isoflurane.…”
Section: Discussionmentioning
confidence: 57%
“…No study found statistically significant differences in brain relaxation scores between desflurane and the other anesthetic agents. Time to eye opening, defined as the time between cessation of the anesthetic agent and eye opening, was reported in 8 studies 9–12,14–17 . Anesthesia with desflurane resulted in significantly shorter times to eye opening in 5 of these 8 studies, 9,14–17 whereas there was no statistically significant differences in eye opening times among the other studies 10–12 .…”
Section: Resultsmentioning
confidence: 99%
“…The results of the primary outcomes are summarized in Table 2. Brain relaxation scores were reported in 5 studies 10,13–16 . For the evaluation of brain relaxation, a score ranging from 1 (completely relaxed brain) to 4 (swollen brain) was used in all studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We intended to include minimum 50 patients in our study as per study by Paul et al [7] to have a statistical power of…”
Section: Discussionmentioning
confidence: 99%